Frontispiece: Investigation of Cycloparaphenylenes (CPPs) and their Noncovalent Ring‐in‐Ring and Fullerene‐in‐Ring Complexes by (Matrix‐Assisted) Laser Desorption/Ionization and Density Functional Theory. Issue 40 (21st July 2020) - Minameyer, Martin B.; Xu, Youzhi; Frühwald, Stefan; Görling, Andreas; von Delius, Max; Drewello, Thomas
Abstract : Direct laser desorption ionization (LDI) is introduced as a straightforward approach for the sensitive analysis of [ n ]cycloparaphenylenes ([ n ]CPPs) and matrix‐assisted LDI (MALDI) as a new sensitive method for analysis of host–guest complexes of CPPs with fullerenes. Novel complexes are detected and selective binding can be observed, reflecting ideal size requirements for efficient complex formation. Fragmentation experiments reveal the charge localization in ionized complexes. Geometries, binding energies and fragmentation energies are derived from DFT calculations. For more information, see the Full Paper by T. Drewello and co‐workers on page 8729 ff.